ANALISIS PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR PAI SISWA SEKOLAH DASAR - Baitus Silmi; Eni Fariyatul Fahyuni; Anita Puji Astutik (LPPM STAI Muhammadiyah Probolinggo, 2022)
Teachers are required to choose a learning model that can help each student to be active and involved in learning. One alternative learning model that allows students to develop thinking skills (reasoning, communication, and connection) in solving problems is problem-based learning (PBL). This model requires students to be creative in carrying out the learning process through group discussions. This study aims to determine the implementation of learning with the PBL model by teachers of Islamic Religious Education (PAI) subjects. The research method used in this research is qualitative. This research was conducted at Glagaharum State Elementary School, Sabililkhoir Ibtidaiyah Madrasah, Plumbon State Elementary School. The main subjects in this study were PAI subject teachers. The results showed that PAI teachers at SDN Glagaharum, MI Sabililkhoir, and SDN Plumbon had implemented the learning steps with the PBL model quite well. PAI teachers always consider the material and students' abilities before giving assignments or problems. The learning process is going well and students are also actively participating in learning.